Two-point Padé approximants to Stieltjes series representation of bulk moduli of regular composites - Tokarzewski, Stanisław; Telega, Józef Joachim (Computer Assisted Methods in Engineering and Science, 1996)
The aim of this contribution is to present two-point Padé approximants method for the determination of upper and lower estimates on the effective transport coefficients of two-phase composite materials. The obtained formulae improve the corresponding one-point Padé approximants bounds [1,2,4,14,23] . As an example, a set of narrowing bounds for the overall conductivity of a square array of cylinders has been evaluated.